2018
DOI: 10.5853/jos.2017.00178
|View full text |Cite|
|
Sign up to set email alerts
|

Penumbral Imaging-Based Thrombolysis with Tenecteplase Is Feasible up to 24 Hours after Symptom Onset

Abstract: Background and Purpose Thrombolysis >4.5 hours after ischemic stroke onset is unproven. We assessed the feasibility of tenecteplase (TNK) treatment in patients with evidence of an ischemic penumbra 4.5 to 24 hours after onset.Methods Acute ischemic stroke patients underwent perfusion computed tomography (CT)/magnetic resonance imaging. Patients with cerebral blood volume (CBV) or diffusion weighted imaging Alberta Stroke Program Early CT Scores (ASPECTS) >6 and mismatch score >2 (defined as >2 ASPECTS regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Michel et al [ 14 ] randomly assigned stroke patients occurring in the middle cerebral artery territory to alteplase venous thrombolysis, with an average last proof of well-being time point of 564 min (9.4 h), or placebo, and an average last proof of well-being of 437.5 min (7.3 h), and the results showed that thrombolytic therapy is feasible in patients with unknown stroke. Kate et al [ 15 ] reported patients were treated with tenecteplase at a median of 9.6 h after symptom onset with a range of 5.1 to 23.7 h and supported the feasibility of tenecteplase treatment in patients with 4 to 24 h of ischemic penumbral onset. In addition, we also performed subgroup analysis through different ages, NIHSS scores, and time windows and demonstrated that patients in the IVT group had better favorable functional outcomes at age ≤70 years, NIHSS ≤10, and time windows >9 h than the patients in the CG.…”
Section: Discussionmentioning
confidence: 98%
“…Michel et al [ 14 ] randomly assigned stroke patients occurring in the middle cerebral artery territory to alteplase venous thrombolysis, with an average last proof of well-being time point of 564 min (9.4 h), or placebo, and an average last proof of well-being of 437.5 min (7.3 h), and the results showed that thrombolytic therapy is feasible in patients with unknown stroke. Kate et al [ 15 ] reported patients were treated with tenecteplase at a median of 9.6 h after symptom onset with a range of 5.1 to 23.7 h and supported the feasibility of tenecteplase treatment in patients with 4 to 24 h of ischemic penumbral onset. In addition, we also performed subgroup analysis through different ages, NIHSS scores, and time windows and demonstrated that patients in the IVT group had better favorable functional outcomes at age ≤70 years, NIHSS ≤10, and time windows >9 h than the patients in the CG.…”
Section: Discussionmentioning
confidence: 98%
“…La mayoría de los centros no cuentan con imágenes avanzadas por lo que la CT de cerebro con ASPECTS ≥ 7 y buen estado de colaterales al CTA orientan a que hay tejido cerebral que puede ser reperfundido a pesar de estar fuera de la ventana terapéutica [14][15][16] . TNK se ha usado en ventana extendida con beneficios hasta 24 horas desde el inicio de los síntomas, con alta tasa de recanalización y baja tasa de complicaciones hemorrágicas 17 .…”
Section: Discussionunclassified
“…The efficacy of EVT treatment for such patients that was proven in recent randomized clinical trials was replicated in our predominantly Asian cohort. Further experience and reports are warranted in implementation of ischemic penumbra quantification and application of recanalization treatments in the era of extended time window [25]. …”
Section: Discussionmentioning
confidence: 99%